Detection of hazardous volatile organic compounds (VOCs) by metal oxide nanostructures-based gas sensors: A review - Mirzaei, A.; Leonardi, S.G.; Neri, G. (Ceramics international, 2016)
Since the sensing capability of semiconducting metal oxides was demonstrated in the 1960s, solid state gas sensors based on these materials have attracted considerable attention from both scientific and practical point of view. Because of the promising characteristics for detecting toxic gases and volatile organic compounds (VOCs) compared to conventional techniques, these devices are expected to play a key role in environmental monitoring, chemical process control, personal safety and so on in the near future. Therefore, in recent years, intensive studies have been conducted to improve their sensing performances, particularly to increase the sensitivity and detection limit of such devices. This can be accomplished by using metal oxide nanostructures with various shapes such as nanoparticles, nanowires, nanorods and nanotubes having sizes in the nanometer range. Owing to the high surface-to-volume ratios and consequently large number of surface sites exposed to target gas, nanostructured metal oxides enable a larger gas-sensing layer interaction and hence a higher sensitivity in comparison with conventional materials. This article extensively reviews recent developments in this field, focusing the attention on the detection of some common VOCs, including acetone (C3H6O), acetylene (C2H2), benzene (C6H6), cyclohexene (C6H10), ethanol (C2H5OH), formaldehyde (HCHO), n-butanol (C4H9OH), methanol (CH3OH) toluene (C7H8), and 2-propanol (C3H8O), by means of conductometric solid state sensors based on nanostructured semiconducting metal oxides.